Platinum group elements in stream sediments of mining zones: The Hex River (Bushveld Igneous Complex, South Africa). (May 2017) - Almécija, Clara; Cobelo-García, Antonio; Wepener, Victor; Prego, Ricardo
Abstract: Assessment of the environmental impact of platinum group elements (PGE) and other trace elements from mining activities is essential to prevent potential environmental risks. This study evaluates the concentrations of PGE in stream sediments of the Hex River, which drains the mining area of the Bushveld Igneous Complex (South Africa), at four sampling points. Major, minor and trace elements (Fe, Ca, Al, Mg, Mn, V, Cr, Zn, Cu, As, Co, Ni, Cd, and Pb) were analyzed by FAAS and ETAAS in suspended particulate matter and different sediment fractions (<63, 63–500 and 500–2000 μm), and Pt, Pd, Rh, and Ir were measured by ICP-MS after removal of interfering elements (cation exchange resin 50W-DOWEX-X8). Procedures were blank-corrected and accuracy checked using reference materials. Nickel, Cr, Pt, Pd, Rh and Ir show concentrations 3-, 13- 18-, 28-, 48- and 44- fold the typical upper continental crust levels, respectively, although lower than concentrations reported for the parent rocks. The highest concentrations were observed closer to the mining area, decreasing with distance and in the <63 μm fraction, probably derived from atmospheric deposition and surface runoff of PGE-rich particles released from mining activities. Thus, mining activities are causing some disturbance of the surface PGE geochemical cycle, increasing the presence of PGE in the fine fraction of river sediments. We propose that indicators such as airborne particulate matter, and soil and river sediment quality, should be added to the protocols for evaluating the sustainability of mining activities. Graphical abstract: Highlights: Mining causes disturbance on the surface geochemical cycle of PGE. The impact of PGE mining activities is mostly on the silt and clay fractions. PGE concentrations decrease with the distance to the mining areas. River sediment quality should be taken into account for assessing mining activities.